Pengalaman Perawat Dalam Menghadapi Dilema Etik Pada Pasien Paliative Di ICU: A Scoping Review - Intan Rizkianti; Lurdes Acorta Freitas; Fitri Sesilia; Kurhayati Kurhayati; Silvestre Dos Reis; Kurnia Nasrullah; Yanny Trisyani (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Nurses in intensive care units (ICU) often face ethical dilemmas when caring for palliative patients. Decisions made at this late stage of a patient's life have a major impact on the quality of life of the patient and their family, and can trigger conflicts between professional values, patient expectations, and family needs. This study aimed toexplore the experiences of ICU nurses in facing ethical dilemmas in palliative patients and to map the main ethicalissues faced. Methods: This study used a scoping review approach with literature search through several databases, such as Pubmed, Ebsco, and Science Direct. The article searches and analysis was from November to December 2024. Inclusion criteria included studies published from 2014-2024 related to ethical dilemmas in palliative care in the ICU, with experimental, case study, and qualitative descriptive research designs. Relevant articles were screened following PRISMA guidelines and analyzed qualitatively descriptively. Of the 19,765 articles identified, 8 articles metthe inclusion criteria and were analyzed further. Nurses faced ethical dilemmas that included conflicts in carrying outprofessional roles, feeling sandwiched between patient wishes and family expectations, and organizational policylimitations. The two main categories found were conflict within the professional role and conflict between personal autonomy and external demands, including pressure from family and coworkers. The importance of improvingeffective communication, emotional support, multidisciplinary teamwork, clinical ethics training and education, developing adaptive coping strategies, and support policies in an effort to minimize the stress experienced by nurses infacing ethical dilemmas in caring for palliative patients. Keywords: Ethics, Nurse, Palliative Care ABSTRAK Perawat di unit perawatan intensif (ICU) sering menghadapi dilema etik ketika merawat pasien paliatif. Keputusan yang diambil pada tahap akhir kehidupan pasien ini memiliki dampak besar terhadap kualitas hidup pasien dan keluarganya, serta dapat memicu konflik antara nilai profesional, harapan pasien, dan kebutuhan keluarga. Penelitian ini bertujuan untuk menggali pengalaman perawat ICU dalam menghadapi dilema etis pada pasien paliatif dan dalammemetakan isu-isu etika utama yang dihadapi. Studi ini menggunakan metode pendekatan scoping review dengan pencarian literature melalui beberapa database, seperti Pubmed, Ebsco, dan Science Direct. Pencarian serta analisis artikel dilakukan bulan November hingga Desember 2024. Dengan Kriteria inklusi meliputi studi yang dipublikasikansejak 2014-2024 yang berkaitan dengan dilema etika dalam perawatan paliatif di ICU, dengan desain penelitian eksperimental, studi kasus, dan deskriptif kualitatif. Artikel yang relevan diseleksi mengikuti pedoman PRISMA dan dianalisis secara kualitatif deskriptif. Dari 19.765 artikel yang teridentifikasi, 8 artikel memenuhi kriteria inklusi dan dianalisis lebih lanjut. Perawat menghadapi dilema etis yang mencakup konflik dalam melaksanakan peran profesional, perasaan terjepit antara keinginan pasien dan harapan keluarga, serta keterbatasan kebijakan organisasi.Dua kategori utama yang ditemukan adalah konflik dalam peran profesional dan konflik antara otonomi pribadi dengan tuntutan eksternal, termasuk tekanan dari keluarga dan rekan kerja. Pentingnya peningkatan komunikasi efektif, dukungan emosional, kerja sama tim multidisplin, pelatihan dan edukasi etik klinik, pengembangan strategi koping adaptif, dan dukungan organisasi dalam upaya meminimalisir stress yang dialami oleh perawat dalam menghadapi dilema etik merawat pasien paliatif. Kata Kunci: Dilema Etik, Perawat, Perawatan Paliatif